2022
DOI: 10.3390/joitmc8020062
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology as a Game Changer for Green Innovation: Green Entrepreneurship as a Roadmap to Green Economic Sustainability in Peru

Abstract: Blockchain technology has been heralded as a game changer for addressing severe environmental and economic sustainability challenges. In response to rising environmental concerns, blockchain technology (BCT) is transforming green innovation, culminating in green economic practices and well-established business models. Recognizing this, we investigated the role of blockchain technology in green innovation practices and its impact on green economic sustainability, which has an impact on green environmental susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 110 publications
(200 reference statements)
1
4
0
Order By: Relevance
“…The emphasis on technology, particularly solar and wind energy, in our study aligns with literature asserting the increasing cost-competitiveness of renewable energy sources with fossil fuels [ 11 , 12 ]. This underlines the continuous need for technological advancement and widespread deployment to meet energy demands sustainably.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The emphasis on technology, particularly solar and wind energy, in our study aligns with literature asserting the increasing cost-competitiveness of renewable energy sources with fossil fuels [ 11 , 12 ]. This underlines the continuous need for technological advancement and widespread deployment to meet energy demands sustainably.…”
Section: Resultssupporting
confidence: 80%
“…This section will analyze technology, politics, financing, and public awareness as key elements of a successful GE economic transition. Technology drives the GE [ 11 ]. Solar and wind energy are becoming cost-competitive with fossil fuels.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Fourth, regarding blockchain technology, Chin et al [ 56 ] found that blockchain technology positively affects green innovation performance, while value appropriation capability also mediates the blockchain technology–green innovation relationship in ecosystem-based business models. Polas et al [ 57 ] investigated the role of blockchain technology in green innovation practices and found that blockchain technology mediates the relationship between sustainability orientation and social perception with the adoption of green innovation that employs green energy technology towards a sustainable green economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By leveraging digital technologies and green development principles, rural entrepreneurs can not only enhance the economic viability of their ventures, but also contribute to the preservation of natural resources and the well-being of local communities [33,34]. Thus, green entrepreneurship has emerged as a vital driver of rural revitalization efforts, aligning with broader goals of promoting inclusive and environmentally sustainable development [35][36][37].…”
Section: Green Entrepreneurshipmentioning
confidence: 99%